2008
DOI: 10.1111/j.1745-7262.2008.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between testosterone and indexes indicating endothelial function in male coronary heart disease patients

Abstract: FT level was inversely correlated with VCAM-1 concentration and IMT which are indicators of endothelial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 20 publications
2
24
0
1
Order By: Relevance
“…However, the mechanism by which cardiometabolic risk increases in patients with hypogonadism remains to be completely elucidated. Inflammation, insulin resistance, and endothelial dysfunction are the major contributors to increased cardiometabolic risk in hypogonadism (4)(5)(6)(7)(8). In our previous studies, we observed that even young patients with hypogonadism exhibit endothelial dysfunction, inflammation, and insulin resistance (9)(10)(11).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, the mechanism by which cardiometabolic risk increases in patients with hypogonadism remains to be completely elucidated. Inflammation, insulin resistance, and endothelial dysfunction are the major contributors to increased cardiometabolic risk in hypogonadism (4)(5)(6)(7)(8). In our previous studies, we observed that even young patients with hypogonadism exhibit endothelial dysfunction, inflammation, and insulin resistance (9)(10)(11).…”
Section: Introductionmentioning
confidence: 86%
“…2017;61/3 fundamental contributors to increased cardiometabolic risk (4)(5)(6)(7)(8). In our previous studies, we reported metabolic derangements and endothelial dysfunction, inflammation, and insulin resistance in young and treatment-naïve patients with hypogonadism (9-11).…”
Section: Vai and Tg/hdl Ratio In Hypogonadismmentioning
confidence: 99%
“…Vascular cell adhesion molecule (VCAM) mediates the migration of macrophages into the intima media and is an integral part of the pathogenesis of fatty streak formation. The levels of this VCAM have been shown to be inversely related to fT [43]. Replacement of testosterone has also been shown to reduce the levels of inflammatory mediators like TNF-alpha and ILbeta that are now considered as important players in atherosclerosis [44].…”
Section: Androgens Atherosclerosis and Coronary Artery Disease (Cad)mentioning
confidence: 97%
“…Although the mechanism of androgen in anti-atherosclerosis is still obscure, on the basis of findings in animal models, it may be speculated to be related to an anti-inflammatory effect, regulation of apoptosis and promotion of smooth muscle cell stability. In humans, a crosssectional study of men aged 50-70 years found that serum testosterone level correlated inversely with the level of vascular cell adhesion molecule-1 (VCAM-1), in addition to CIMT [32]. Endothelial cells produce VCAM-1 by stimulation of inflammatory cytokines such as tumor necrosis factor-α and interleukin-1 and so, the expression of VCAM-1 increases during inflammation.…”
Section: May Bementioning
confidence: 99%